Public Laws and Private Lawmakers - Kimberly N. Brown (Washington University Law Review, 2016)
The Obama Administration’s “Clean Power Plan” for addressing industrial carbon emissions is controversial as a matter of environmental policy. It also has important constitutional implications. The rule was initially crafted not by officers or employees of the Environmental Protection Agency, but by two private lawyers and a scientist with industry ties. Private parties operate extra-constitutionally, and no existing legal doctrine tethers constitutional scrutiny to the nature of the power delegated to them. The nondelegation doctrine applies to delegations by Congress—not to agencies’ subdelegations of legislative power to private parties. The other doctrinal lens for reviewing rulemaking by entities other than Congress—Chevron U.S.A. v. National Resources Defense Council, Inc. and its progeny—is equally blind to subdelegations of policymaking authority to parties that function beyond the boundaries of the Constitution. This Article takes up the issue of private rulemaking, and argues that its inescapable constitutional implications warrant a stronger nondelegation doctrine and a more nuanced approach to Chevron that emphasizes public accountability, legitimacy, transparency, and rational decision-making over notions of agency prerogative.
Keywords: Clean Power Plan; Chevron deference; Chevron U.S.A. v. National Resources Defense Council; EPA; Private lawmaking; Agency sub-delegation; Constitutional Law; Administrative Law; Environmental Law